Qualitative study of stakeholder influence on environmental practices: evidence from the Malaysian aviation industry - Zakaria, Zarina; Zakaria, Zamzulaila (Nova Southeastern University, 2024)
In this study, we seek to explore the influence of stakeholders on environmental management practices in Malaysia's aviation industry. The data from this study was derived from interviewing 25 respondents in nine organisations within the aviation sector and was analysed using thematic analysis. We show that internal and external stakeholders significantly influence changes towards better environmental management practices. While internal stakeholders have contributed to better environmental management practices by changing their day-to-day practices within their functional role in the organisation, the external stakeholders have been the key actors that have significantly pushed the organisation to implement a proper environmental management system (EMS), particularly the role played by the regulatory authorities in ensuring compliance with environmental standards. We also highlight that the tension between economic and ecological elements may limit the extent of environmental practices carried out by the aviation sector; nonetheless, continuous engagement and pressure from the community and non-governmental organisations (NGOs) may push the aviation sector to revisit their commitment to environmental practices beyond compliance activities to ecological standards.